My silver stripes and other poems - Emsley, Maletšema Ruth (Staging Post, a division of Jacana Media (Pty) Ltd, 2023)
Refer to the book
Book
Keywords: Poetry; African poetry; English poetry -- Black authors; African poetry (English); Conduct of life -- Poetry; Women in literature